The utilisation of feed and byproducts of mineral carbonation processes as pozzolanic cement replacements. (10th June 2018) - Benhelal, E.; Rashid, M.I.; Holt, C.; Rayson, M.S.; Brent, G.; Hook, J.M.; Stockenhuber, M.; Kennedy, E.M.
Abstract: Utilising the byproducts of mineral carbonation processes contributes to rendering the technology environmentally benign and enhances the economically viability of the process. In this work we synthesised, characterised and investigated the technical feasibility and environmental benefits of utilising feed and byproducts of mineral carbonation technology as Portland cement substitutes. These materials, with and without pre-treatment, were used to substitute 5, 10 and 20 wt% of Portland cement in mortars. Pozzolanic activity tests indicated that acid treated silica enriched residue (ATSER) displayed pozzolanic activity. At 5% cement replacement all materials showed compressive strengths comparable to the control. When 10 wt% of cement was replaced, only heat activated lizardite showed strength results similar to the control. The compressive strength of mortars containing other samples with 10 wt% or greater cement replacement showed that the extra water demand outweighed any pozzolanic contribution of mineral carbonation materials and resulted in a lowering of the compressive strength of these mortars compared to controls, in particular when in excess of 10 wt% of cement is replaced. An environmental analysis showed that in addition to significant CO2 emissions reduction, the economic and environmental costs of waste disposal were avoided when mineral carbonation byproducts substituted Portland cement. Highlights: Results of Si extraction at pH∼13.5 indicated ATSER had the fastest rate of Si extraction even higher than silica fume. Pozzolanic activity tests showed that ATSER displayed some level of pozzolanic activity slightly less than silica fume. 5 wt% cement replacement with mineral carbonation materials showed acceptable compressive strength for all subsitutes. 10 wt% or higher cement replacement resulted in lower strength compared to the control.